PENGARUH OLAHAN MESIN ESPRESSO DAN MANUAL BREW POUR OVER V60 PADA BIJI KOPI ARABIKA (Coffea arabica L) TERHADAP AKTIVITAS ANTIOKSIDAN - Syarifuddin K.A; Yusriyani Yusriyani (Jurnal Kesehatan Yamasi Makassar, 2022)
Arabica coffee (Coffea arabica L) adalah coffee bean extract drink that has been roasted and ground into a powder. Arabica coffee beans contains saponins, phenols, chlorogenic acid, mangiferin and flavonoids which show antioxidant activity. This study aims to determine the effect of processed espresso machine and manual brew pour over V60 on Arabica coffee beans on antioxidant activity and to determine the IC50 value of espresso filtrate and pour over V60 on Arabica coffee beans (Coffea arabica L). The antioxidant activity test used the DPPH (1,1-diphenyl-2-picrylhydrazyl) method. Based on the research results, it shows that the IC50 values ​​of espresso and pour over V60 filtrate are 324,289 ppm and 447,352 ppm. So that the highest antioxidant activity is found in the espresso filtrate.